Application and challenges of 3D food printing technology in manned spaceflight: a review - Zhang, Long‐zhen; Dong, Hai‐sheng; Yu, Yan‐bo; Liu, Li‐yan; Zang, Peng (International journal of food science & technology, 2022)
Summary Three‐dimensional (3D) food printing is a digital food engineering method that has a remarkable application potential in long‐term manned spaceflight. Extrusion‐based 3D food printing, among the available 3D food printing techniques utilised in the food industry, is one of the most suitable printing methods for manned spaceflight. Extrusion‐based 3D food printing could suffice most of the energy and personalised nutritional requirements of astronauts during long‐term stay in space by utilising fruits, vegetables, meat products, and nutrients as printing materials. However, 3D food printing in manned spaceflight is still limited by technologies and costs such as printing materials, microgravity, post‐processability of food, and engineering transportation under the existing technical conditions. Therefore, this article reviews the 3D food printing and manned spaceflight technologies that are currently available and discusses the challenges involved in 3D food printing in manned spaceflight, thus providing a theoretical basis for future 3D food printing for space missions.